CASH FLOW MANAGEMENT IN JOINT-STOCK COMPANIES: PRINCIPLES, CHALLENGES, AND DIGITAL STRATEGIES (E Global Congress, 2025)
This article examines the principles and modern practices of cash flow management in joint-stock companies (JSCs), emphasizing its importance for financial stability, investment attractiveness, and sustainable growth. Cash flow — the movement of money into and out of a company — is a key indicator of its operational efficiency and financial health. Joint-stock companies, due to their shareholder structure and larger operational scale, require precise and strategic cash management mechanisms. The article analyzes core components such as operating, investing, and financing cash flows; identifies common challenges; and explores innovative digital tools used in forecasting and optimization. Special attention is given to the experience of emerging markets, including Uzbekistan, where regulatory reforms and digital transformation are reshaping the cash flow management landscape in corporate finance.